Time Management and Employee Productivity in Government Institutions in Delta State - ODOH, Christabel O. (International Journal of Public Administration Studies, 2023)
The value of time management lies in the fact that people have too many tasks they need to do but not enough time for the things that they want to do. The study therefore, examined time management and employee productivity in government institutions in Delta State. The study adopted Time Management Quadrant theory. The study utilized secondary source of data. The study revealed that effective time management not only affects the productivity of employees, but also helps to cope with stress, conflicts and pressure more efficiently. It also helps them maintain a healthy work-life balance and keeps them motivated. The recommended that time should be set for the accomplishment of all activities by government at all levels including the core ministries. Adequate provisions should be made for the attainment of the goals set, among others.